Saudi EFL Students’ Perception of the Quality of Teacher-Student Relationships and the Factors that Impact Their Self-Efficacy Beliefs - Almalki, Mashael Ahmed; Althaqafi, Abeer Sultan (Global Journal of Educational Studies, 2024)
This study aimed to explore the perceptions of English as Foreign Language (EFL) students in the Preparatory Year Program (PYP) at a Saudi university about emotional quality of teacher-student relationships and the factors that impact their self-efficacy beliefs in EFL classrooms. To accomplish this, an explanatory sequential mixed methods approach was implemented. Starting with a quantitative approach a questionnaire was distributed to 340 EFL students followed by a qualitative approach in terms of 8 semi-structured interviews were conducted to explore the students’ perceptions. The quantitative data were analyzed statistically using SPSS and the transcribed interviews were coded manually after which a thematic analysis was used to extract the emerging themes. The results demonstrated that students have a positive relationship with their teachers in EFL classrooms and they view their English language teachers as reassuring, reliable, and trustworthy. Students also believe that their relationship with their teachers influences both their academic and personal growth. Finally, the outcomes of this study also showed that students believe that relationship with their significant others, teachers- peers- family members, and outcome expectancy impact their self-efficacy greatly in EFL classrooms. This research provides insight into the emotional quality of teacher-student relationships and students’ self-efficacy in EFL classes, and the findings provide insights that can inform teaching strategies, curriculum development, organizations, and learner support systems.